Effect of the 2017 European Guidelines on Reclassification of Severe Aortic Stenosis and Its Influence on Management Decisions for Initially Asymptomatic Aortic Stenosis. (December 2020) - Chan, Daniel C.S.; Singh, Anvesha; Greenwood, John P.; Dawson, Dana K.; Lang, Chim C.; Berry, Colin; Pakkal, Mini; Everett, Russell J.; Dweck, Marc R.; Ng, Leong L.; McCann, Gerry P.
Abstract : Background: The 2017 European Society of Cardiology guidelines for valvular heart disease included changes in the definition of severe aortic stenosis (AS). We wanted to evaluate its influence on management decisions in asymptomatic patients with moderate-severe AS. Methods: We reclassified the AS severity of the participants of the PRIMID-AS study (Prognostic Importance of Microvascular Dysfunction in Asymptomatic Patients With AS), using the 2017 guidelines, determined their risk of reaching a clinical end point (valve replacement for symptoms, hospitalization, or cardiovascular death) and evaluated the prognostic value of aortic valve calcium score and biomarkers. Patients underwent echocardiography, cardiac magnetic resonance imaging, exercise tolerance testing, and biomarker assessment. Results: Of the 174 participants, 45% (56/124) classified as severe AS were reclassified as moderate AS. This reclassified group was similar to the original moderate group in clinical characteristics, gradients, calcium scores, and remodeling parameters. There were 47 primary end points (41 valve replacement, 1 death, and 5 hospitalizations—1 chest pain, 2 dyspnea, 1 heart failure, and 1 syncope) over 368±156 days follow-up. The severe and reclassified groups had a higher risk compared with moderate group (adjusted hazard ratio 4.95 [2.02–12.13] and 2.78 [1.07–7.22], respectively), with the reclassified group demonstrating an intermediate risk. A mean pressure gradient ≥31 mm Hg had a 7× higher risk of the primary end point in the reclassified group. Aortic valve calcium score was more prognostic in females and low valve area but not after adjusting for gradients. NT-proBNP (N-terminal pro-brain-type natriuretic peptide) and myocardial perfusion reserve were associated with the primary end point but not after adjusting for positive exercise tolerance testing. Troponin was associated with cardiovascular death or unplanned hospitalizations. Conclusions: Reclassification of asymptomatic severe AS into moderate AS was common using the European Society of Cardiology 2017 guidelines. This group had an intermediate risk of reaching the primary end point. Exercise testing, multimodality imaging, and lower mean pressure gradient threshold of 31 mm Hg may improve risk stratification. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01658345. Abstract : Supplemental Digital Content is available in the text.